1999
DOI: 10.1038/sj.ejhg.5200390
|View full text |Cite
|
Sign up to set email alerts
|

Smith-Lemli-Opitz syndrome: evidence of T93M as a common mutation of Δ7-sterol reductase in Italy and report of three novel mutations

Abstract: The Smith-Lemli-Opitz syndrome (SLOS) is an autosomal recessive disorder of cholesterol biosynthesis characterised by facial dysmorphisms, mental retardation and multiple congenital anomalies. SLOS is caused by mutations of the human ∆7-sterol reductase (DHCR7) gene and, so far, 19 different mutations have been described. Among these, mutations impairing the activity of the C-terminus appear to be the most severe. Here we report the mutational analysis of the DHCR7 gene in nine Italian SLOS patients. The T93M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…This mutation is obviously rare in South and East Europe. It was not observed among 18 SLOS alleles from southern Italy 24 and is rare in Poland (see Table 1). Its frequency increased towards the northwest.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…This mutation is obviously rare in South and East Europe. It was not observed among 18 SLOS alleles from southern Italy 24 and is rare in Poland (see Table 1). Its frequency increased towards the northwest.…”
Section: Discussionmentioning
confidence: 97%
“…Twenty-six of these have been previously identified by us 15,18 and others. 16,17,19,[24][25][26] Six of the mutations have not been described before (T154R, M270V, G309S, R443H, I178N, R242H). No mutation was found on four out of 118 SLOS chromosomes from four patients (96.6% mutation-detection rate).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The net production of cholesterol is catalyzed by a delta-7-sterol reductase (DHCR7, 7-dehydrocholesterol reductase), a NADPH dependent oxidoreductase located at the endoplasmic reticulum (ER). As a cholesterol-synthesising enzyme, interest has grown in DHCR7 since its discovery as the product of the gene mutated in the Smith-LemliOpitz syndrome (SLOS) Wassif et al, 1998;De Brasi et al, 1999), which was first identified in 1964 as a recessive malformation/mental retardation syndrome (Nowaczyk and Waye, 2001;Prasad et al, 2002;Jira et al, 2003;Nowaczyk et al, 2004). Until now, isolation of DHCR7 cDNA has been reported for several species including humans, mice Moebius et al, 1998), rats (Bae et al, 1999), and Arabidopsis (Lecain et al, 1996).…”
Section: Introductionmentioning
confidence: 99%